2023
DOI: 10.1101/2023.04.25.23289027
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping of the gene network that regulates glycan clock of ageing

Abstract: Glycans are an essential structural component of Immunoglobulin G (IgG) that modulate its structure and function. However, regulatory mechanisms behind this complex posttranslational modification are not well known. Previous genome-wide association studies (GWAS) identified 29 genomic regions involved in regulation of IgG glycosylation, but only a few were functionally validated. One of the key functional features of IgG glycosylation is the addition of galactose (galactosylation). We performed GWAS of IgG gal… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 87 publications
3
3
0
Order By: Relevance
“…Moreover, a key glycosyltransferase, B4GALT1 (β-1,4-galactosyltransferase 1), which catalyzes the addition of galactose, had a completely different pattern of expression in two analyzed experiments from the pattern of IgG galactosylation ( Figure 3 ). This was in line with previous genome-wide association studies (GWAS) of IgG glycosylation, which discovered that many genetic loci that associate with IgG glycosylation have no known role in the process of glycosylation [ 49 , 50 , 51 , 52 , 53 ]. So, we integrated the data from different GWA studies of IgG glycosylation and focused on changes of expression in IgG glycome GWAS hits in our two time course experiments.…”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…Moreover, a key glycosyltransferase, B4GALT1 (β-1,4-galactosyltransferase 1), which catalyzes the addition of galactose, had a completely different pattern of expression in two analyzed experiments from the pattern of IgG galactosylation ( Figure 3 ). This was in line with previous genome-wide association studies (GWAS) of IgG glycosylation, which discovered that many genetic loci that associate with IgG glycosylation have no known role in the process of glycosylation [ 49 , 50 , 51 , 52 , 53 ]. So, we integrated the data from different GWA studies of IgG glycosylation and focused on changes of expression in IgG glycome GWAS hits in our two time course experiments.…”
Section: Resultssupporting
confidence: 87%
“…At the same time, we found that the upregulation of another galactosylation-associated gene, SPINK4, led only to a decrease of G1 structures in the IgG glycome [65]. A different pattern of change for G1 and G2 glycans was also observed in consecutive studies performed in our lab [44,53,65]. Taken together, these results suggest that different regulatory mechanisms control IgG mono-and digalactosylation.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations